A practical guide for edTPA implementation : lessons from the field - Barron, Lisa (Associate professor of teacher education) (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
edTPA is the most widely-used performance assessment for pre-service teachers in the United States, and a requirement in many states for teaching licensure. Through edTPA, teacher candidates demonstrate their effectiveness in different aspects of teaching, including planning, instruction, assessment, analysis of teaching, and use of academic language.This book is a practical guide for anyone involved in edTPA implementation. The chapters are written by experienced teacher educators who are leading successful edTPA programs in their own universities, who are in the field, and involved in the work. They represent diverse teacher preparation programs, each with their own strengths and challenges. This book addresses the challenges of edTPA, while providing practical strategies for educative and thoughtful implementation. Organized into four sections, each section explores a different aspect of edTPA implementation, and provides guidance for leading faculty and teacher candidates through edTPA.